PEl'lGEMBANGAN INTELLECTUAL CAPITAL DAN SOCIAL CAPITAL MELALUI PENDIDIKAN KEWARGANEGARAAN - Suyato, Suyato (Jurnal Cakrawala Pendidikan, 2016)
Developing intellectu,,1 and social capital in preparing student for their future's role as constructive and critical citizen is essential in a healthy de~ocratic state, School-based civic education ,as one of means in building such ones faces some challenges, Developing intellectual and capital, may be, is the greatest one. This paper tries to propose the urgency of such effort by arguing that school"based civic education Can be utilized as a means of making well informed citizen, The main concepts, such as democracy, citizenship, and responsibilities of government should be understood by citizen properly and comprehensively. Therefore, the paramount challenge of civic education teachers is how to implement a teaching strategy for best instilling those values, because people are not born with the knowledge, skills, and attitudes necessary to make democracy work; rather, they acquire this knowledge and capacity for democratic citizenship .only Ihrough experience,especially through 'School-based civic educa.tion, One of the best strategies of civic education is portfolio-based teaching strategy. In this activity, students have an opportunity to practicing their values related to deIrtocracy, citizen, and responsibility of government. Besides its disadvantages, portfolio based teaching strategy is a promising one in order to prepare the well informed citizen very needed in a healthy democratic 'State. Accordingly, teachers of civic education should change their circumstances by implementing this strategy